Arabic lexicon in Sundanese language: An ethnolinguistic study on the pilgrimage ceremony of the indigenous people in Dukuh village - Husnul Qodim; Fajar Rohandy; Eri Kurniawan (Indonesian Journal of Applied Linguistics, 2022)
The fact that a large number of Arabic loanwords exist in Indonesian-type languages has been public knowledge; however, the number of studies about the types of Arabic lexical items, and their meaning shifts particularly in the Sundanese language is surprisingly scant. To occupy such an empirical void, the present study explores the use of Arabic lexicon in Sundanese language variety spoken by the indigenous people of the Dukuh Village in Cikelet District, Garut Regency, Indonesia. Embracing an ethnolinguistic lens, this study sought to specifically examine the use of their Arabic lexicon, lexical meanings, contextual meanings, and cultural phenomena surrounding the use. A corpus from daily spoken interactions involving ten informants and monologs from elderlies in the Dukuh community serves as the data to be qualitatively analyzed. The results demonstrate that the Arabic loanwords appear in a relatively significant amount of their Sundanese language, 7.37% of the total words in the corpus. Some of the Arabic lexicons retain their meanings identical to those in the source language. However, some have been contextualized so that their meanings somewhat deviated from those of the source language. The Arabic words are evidently found in three main cultural phenomena, i.e., ideas, activities, and artifacts.